Malignant appearance of trichilemmal cyst: a case report with review of the literature - Rajoo, Theyveeka Selvy; Hui Min, Michelle Yong; Tangaraju, Kasturi Nair; Khairy, Azuddin M. (International Surgery Journal, 2023)
69 years old male presented with one month history of non-tender, nodular, pinkish left neck swelling, measuring 10×20 mm. CECT revealed left neck dermatofibrosarcoma protuberans with submandibular vascular malformation. Surgical wide local excision of the lesion and split skin graft was done. Histopathology confirmed trichilemmal cyst (TC). TC is adnexal lesions, found in hair bearing areas. Pinkus pointed out that TC are keratin-filled cysts with a wall resembling the external root sheath of hair follicle. 2% can develop into proliferating trichilemmal tumours (PTTs) and malignant proliferating trichilemmal tumours (MPTTs). PTTs were originally described by Jones as benign but locally aggressive skin neoplasms. Female to male preponderance of 6% to 1%, with average age of 65 years at presentation. 90% are located on the scalp, while the residual 10% occur mainly on the back but they can develop any part of the body such as submandibular region. Proliferating TCs present as lobulated masses, soft in consistency. The masses may become exophytic, ulceration and may show malignant transformation. On imaging, these lesions can be either cystic or solid mass. Histopathological, it is characterised by absence of intercellular bridges between epithelial cells lining the cyst wall. Cyst cavity contains amorphous eosinophilic keratin. Satyaprakash et al report, complete surgical excision is warranted for TCs as if there is proliferative or malignant potential, it would affect the postoperative management and overall prognosis. TC, locally aggressive skin neoplasms and rarely, occurrence at submandibular region or become malignant and appropriately managed to prevent recurrence.